Guyana : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guyana. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights the expansion of Guyana's real economic activity by 3.3 percent in 2016. Subdued agricultural commodity prices, bad weather, and delays in public investment weighed down activity, while large increases in gold output helped support growth. Consumer prices increased by 1.5 percent in the 12 months ending in December 2016 as weather-related shocks to food prices reversed the deflationary trend. The macroeconomic outlook is positive for 2017 and the medium term. Growth is projected at 3.5 percent in 2017, supported by an increase in public investment, continued expansion in the extractive sector, and a recovery in rice production.